Rare bird documentation form for Greater Scaup at Bays Branch, 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
Rare bird documentation form for a Greater Scaup at Bays Branch in Guthrie County, IA on March 21, 1980. Epson - sheet feed